Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let us consider three sequences $(a_n)_{n\ge1}$, $(b_n)_{n\ge1}$ and $(c_n)_{n\ge1}$ having the properties:

  • $a_{n},\ b_{n},\ c_{n}\in\left(0,\ \infty\right)$
  • $a_{n}+b_{n}+c_{n}\ge\frac{a_{n}}{b_{n}}+\frac{b_{n}}{c_{n}}+\frac{c_{n}}{a_{n}}\ \forall n\ge1$
  • $\lim\limits_{n\to\infty}a_{n}b_{n}c_{n}=1 $

Prove that $$\lim_{n\to\infty}\frac{a_{n}+b_{n}+c_{n}}{a_{n}b_{n}+b_{n}c_{n}+c_{n}a_{n}}=1 $$

share|improve this question
    
I first guessed that $a_n,b_n,c_n\to1$, but now I think it might be wrong. I can only show that, when $abc=1$, we have $a/b+b/c+c/a\ge a+b+c$. It suffics to prove that $a/b+a/b+b/c\ge3a$, where AM-GM works. –  Frank Science Jun 24 '12 at 16:33
9  
What is the purpose of the word "own" in the title? –  Byron Schmuland Jun 25 '12 at 16:02
    
@ByronSchmuland Maybe he's finding a pretty proof for his own result. –  Frank Science Jun 26 '12 at 3:20
2  
@ClaudiuMindrila As you can see, in our community, the information that your problem is original is not posted by a code word in the title. That information, and the fact that you have a proof and are looking for alternatives goes into the body of the question. –  Byron Schmuland Jun 26 '12 at 18:59
1  
@ClaudiuMindrila I should add: welcome to MSE! You have nice problems. –  Byron Schmuland Jun 26 '12 at 19:01

1 Answer 1

A proof that isn't very clever but does the job: let $$f(a,b,c)=ab\left(a+b+c-\tfrac ab-\tfrac bc-\tfrac ca\right)$$ which is chosen so that $f(a_n,b_n,c_n)\ge 0$.

The idea is:

  1. Reduce to the $abc=1$ case by defining $g(a,b)=f(a,b,\frac{1}{ab})$ and proving that $f(a_n,b_n,c_n)-g(a_n,b_n)\to 0$.
  2. Prove that $g$ is nonpositive and that $g(a_n,b_n)\to 0$ implies $(a_n,b_n)\to (1,1)$.
  3. Conclude that $(a_n,b_n,c_n)\to (1,1,1)$.

Proof:

  1. Since the problem is invariant under cyclic permutation of $a_n,b_n,c_n$ for any single $n$, we can assume that $c_n$ is the maximum. We get $$c_n/a_n\le a_n+b_n+c_n\le 3c_n\\ 1/a_n\le 3$$ This implies $\limsup b_n c_n\le 3$, so that $$\limsup a_n^2 b_n^3\le \limsup c_n^2 b_n^{5/2} c_n^{1/2}\le 3^{5/2}$$ So: $$a_n^2 b_n^3\left(\tfrac{1}{a_nb_nc_n}-1\right)+\tfrac{1}{a_n}(a_nb_nc_n-1)\to 0$$ and therefore $$f(a_n,b_n,c_n)-g(a_n,b_n)\to 0$$

  2. A straightforward calculation shows that $g(a,b)$ is the cubic polynomial $$-(ab)^3+(ab)^2+a^3b-a^3+a-1$$ with discriminant in $a$ $$-(b-1)^2(b+1)(23b^3+5b^2-27b+23)$$ so that, on $D=[0,+\infty)^2$, $g(a,b)$ is always non-zero when $b\ne 1$, and when $b=1$ it is non-zero only when $a=1$. Therefore because $g(a,b)$ is negative at $(0,0)$ it is everywhere negative except at $(a,b)=(1,1)$.

    Furthermore the $\sup$ of $g$ over $D$ minus any neighborhood of $(1,1)$ is negative because $D$ is closed and $g\le -1+\varepsilon$ in a neighborhood of $\infty$. As a consequence, if $g(a_n,b_n)\to 0$ then $(a_n,b_n)\to (1,1)$.

  3. Because $f(a_n,b_n,c_n)\ge 0$ and $g$ is nonpositive, $g(a_n,b_n)\to 0$, so that $(a_n,b_n)\to (1,1)$ and therefore: $$\lim_{n\to\infty} a_n=\lim_{n\to\infty} b_n=\lim_{n\to\infty} c_n=1$$ which is actually a stronger form of the theorem.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.